Effects of a strength protocol combined with electrical stimulation on patellar tendinopathy: 42 months retrospective follow-up on 6 high-level jumping athletes - Basas, Á.; Cook, J.; Gómez, M. A.; Rafael, M. A.; Ramirez, C.; Medeiros, B.; Lorenzo, A. (Physical Therapy in Sport, 2018)
Study design:A retrospective study. Introduction:Patellar tendinopathy (PT) or jumper's knee (JK) in elite athletes is a challenging condition for sports medicine professionals. This study analyzes the development of a protocol using eccentric, isometric, concentric exercises, and electrostimulation to treat elite athletes suffering from JK. The semiannual strength protocol was completed during a total of 36 months by six high-level jumping athletes with chronic painful JK. Pain during patellar tendon loading activity was evaluated on a visual analogue pain scale (VAS). Upon protocol completion, promising clinical results were evidenced by significant pain reduction during tendon loading activity. Material and methods: Six high level jumping athletes with chronic painful JK completed a semiannual strength program using eccentric, isometric, concentric and electrical stimulation exercises. The protocol was done 12 weeks in the winter pre-season and 10 weeks in the summer pre-season, for altogether 36 months, with an interruption of the protocol at 24 months for 6 months. Pain during patellar tendon loading activity was evaluated on a visual analogue pain scale (VAS), before the first session and then every 6 months, coinciding with the competitive phase, the time of maximum pain. Results: There was a significant (p<0.01) decrease in the VAS from start to the 18, 24 and 48 months follow-ups. Conclusions: In a small group of high level jumping athletes with chronic painful JK, a strength protocol combined with electrical stimulation showed promising clinical results with significant pain reduction during tendon loading activity.